"The Female Character and its Relationship with the Narrative Components in the Novel ’Samar Al-Layali’ by Nabil Suleiman - دواي رنا (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research is concerned with studying the female character in the novel by the writer Nabil Suleiman, “Samar Al-Layali”, especially since the novelistic text needs different types of characters that influence the events of the novel, and work hard to accelerate the movement of events and develop them, and this in turn prompts critics to launch some qualities that determine the ranks of these characters, especially since these characters are known for their relationships with other characters, in addition to the contents and references that form them.